ANALISIS PUISI HERI ISNAINI “PRANGKO” DENGAN PENDEKATAN SEMIOTIKA - Puji Nurul Amalia Putri; Tiana Puspitasari; Indra Permana (IKIP Siliwangi, 2019)
Fiction in literary works in the form of essays or experiences that can be devoted to an article using interesting language, not standardized. Poetry, one of the forms of fiction, contains implicit meaning. Poetry can motivate writing lovers, especially readers who are interested in knowing the meaning of the implicit meaning of a poem through analysis. Based on the previous explanation, the author was interested in conducting a study, namely analyzing the poem by Heri Isnaini entitled